MERCOSUL: INTEGRAÇÃO ECONÔMICA E SETOR DE MÁQUINAS AGRÍCOLAS AUTOMOTRIZES - BRUM, ARGEMIRO L.; PETRY, DÉBORA C.; SOUZA, JOSE D. D. S.; KUNZ, JULIANE; ZINGLER, KARINE D.; FILHO, MAURICIO R. C. (Salão do Conhecimento, 2013)
Resumo